Efficiency of Shopee logistic partners affecting the past-purchases satisfaction of its clients - Arena, Mary Corine, Gariando, Ma. Cassandra, Ulanday, Shaniña, Villamayor, Anne Rose 4 0 16; 5
The number of internet users in the Philippines is steadily increasing, and many smail businesses have embraced online platforms like Shopee for their operations This studyaims to provide an overview of the efficiency of Shopee's logistics partners, and the level of satisfaction experienced by customers after their purchase. The primary objective is to investigate the factors that directly influence customer satisfaction regarding logistics services. To achieve this, the researchers employed purposive sampling to select survey participants who met the study's criteria and had access to relevant demographic information. The results indicate a significant relationship between Shopee's logistics services and post-purchase satisfaction among consumers. Among the various coordination options, J&T Express emerged as the preferred choice for most respondents. The key factors contributingto high satisfaction levels were swift delivery, receipt of products in good condition, undamaged packaging, and secure packaging of goods. Overall, the findings suggest that customers are satisfied with the performance of Shopee's coordination services.
Undergraduate Thesis: (BSBA major in Marketing Management) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2